2015
DOI: 10.1515/prilozi-2015-0089
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Analysis of the Mechanical Properties between the Fiber-Reinforced Composite and Zirconium Posts

Abstract: The longest diameter of the posts significantly increases the resistance to fracture in relation to the two smaller diameters. The larger diameter, the higher values of the bending strength, as well as the lowest values of the tensile strength of the material contribute to improved mechanical properties of the fiber and zirconium posts.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 21 publications
0
2
0
Order By: Relevance
“…Authors have shown that the teeth which are restored with glass‐fibre posts have equal to or greater fracture resistance than the teeth restored with metal posts 9,10 . Zirconia has been considered as an alternative for anterior post‐core restorations because of its aesthetic properties 11 . While the application of glass‐fibre and zirconia post systems has always been a matter of debate, these posts have been shown to have the same fracture resistances 12,13 …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Authors have shown that the teeth which are restored with glass‐fibre posts have equal to or greater fracture resistance than the teeth restored with metal posts 9,10 . Zirconia has been considered as an alternative for anterior post‐core restorations because of its aesthetic properties 11 . While the application of glass‐fibre and zirconia post systems has always been a matter of debate, these posts have been shown to have the same fracture resistances 12,13 …”
Section: Introductionmentioning
confidence: 99%
“…9,10 Zirconia has been considered as an alternative for anterior post-core restorations because of its aesthetic properties. 11 While the application of glass-fibre and zirconia post systems has always been a matter of debate, these posts have been shown to have the same fracture resistances. 12,13 The lack of clear information about the ideal material and size for post-cores enables new materials to be studied in this area.…”
mentioning
confidence: 99%